Knowledge and Perception of Caregivers about Risk Factors and Manifestations of Pneumonia among Under Five Children in Butaleja District, Eastern Uganda - Aguti, Beatrice; Kalema, Godfrey; Lutwama, Dinah Maria; Mawejje, Martin Loy; Mupeyi, Emmanuel; Okanya, David; Nekaka, Rebecca (Microbiology Research Journal International, 2018)
Despite the widespread national intervention strategies to curb its occurrence, Pneumonia remains one of the leading causes of morbidity in Butaleja district. This was a crosssectional study carried out at Busolwe Hospital and aimed at establishing the knowledge and perception of caregivers about risk factors and manifestations of childhood pneumonia and it's high prevalence among the under-five children (U5C) in the district. Methods: Structured researcher administered questionnaires were given to 302 caregivers of U5C visiting the hospital who were enrolled on a continuous random basis from April to May 2018. Microsoft Excel was used to retrieve and analyze the data which was then represented in form of frequencies and proportions. Results: The study found that the majority of caregivers had inadequate knowledge about the condition, despite 69.5% of their U5C having suffered from pneumonia in the previous year. Additionally, some of the contributing factors to the high prevalence of pneumonia included poor ventilation in the houses, the presence of swamps contributing to coldness, failure to complete the immunisation dose and overcrowding in the households leading to household air pollution. Conclusion: Pneumonia remains a big health challenge in Butaleja District as evidenced by the knowledge gap among caregivers as well other contributing factors which lead to its increased prevalence. In order reduce the burden, a comprehensive community sensitisation program needs to be rolled out to address most of the factors. It would also be important to look into the possible misdiagnosis of the condition and rule out antibiotic resistance to come up with an effective management strategy for curbing the high prevalence of pneumonia among the U5C in Butaleja District. Finally, the establishment of a National Health Insurance Scheme is strongly recommended
Keywords: Pneumonia; Butaleja District; Under five children; Knowledge; Caregivers; Immunization status; COBERS